Knowledge and compliance towards alendronate therapy among postmenopausal women with osteoporosis in Palestine - Asma Radwan; Naser Shraim; Josephean Elaraj; Anwar Hamad; Dana Fatayer; Bayan Jarar; Ayoub Johar; Areen Zriqah (BMC, 2022)
Abstract Background Postmenopausal women compliance to alendronate therapy is suboptimal due to the complex dosing requirements. The poor compliance may increase their potential of fractures and the prevalence of side effects. In this study, the compliance of osteoporotic women on bisphosphonate therapy to the complex dosing instructions and their knowledge of alendronate-interactions were assessed. Methods This is a cross-sectional study, using self-administered questionnaire involving 224 osteoporotic women on alendronate therapy, who visited the orthopedic clinics and community pharmacies in the West Bank. Data was collected using a validated questionnaire consisting of 4 sections and analyzed by descriptive statistics. Moreover, associations between patient's socio-demographic characteristics and the extent of compliance and knowledge of alendronate interactions are established in this study. Results A total of 300 questionnaires were distributed and 224 were completed. The median compliance score to alendronate dosing instructions was 5 out of a possible maximum 7, and the median knowledge score about alendronate interactions was 7 out of a possible maximum 14. Factors found to affect either or both the knowledge and compliance to alendronate dosing instructions were, residency, and the source of instructions. Conclusion This study identified the importance of compliance and knowledge gaps among postmenopausal women treated with alendronate. Therefore, appropriate knowledge about the importance of proper compliance to dosing instructions and avoidance of interactions is of a great benefit for maximizing clinical effectiveness, lowering fracture risk and prevention of adverse effects of alendronate among patients treated with alendronate in Palestine.